An Introduction and Critique of Linguistics and the Novel - Golrokh Saeednia (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is an introduction and critical review of the Farsi translation (by Mohammad Ghaffary, 2nd edition) of Roger Fowler’s book “Linguistics and the Novel”. It also introduces briefly the backgrounds of the main ideas discussed in the book. In this regard, a brief discussion of linguistics criticism and the critical translation are covered, with Fowler being an expert on the latter subject as well. Doing research on Fowler’s postulations can be seen in the works of other fields in humanities, such as linguistics and sociology.  In this study, it is attempted to use a formalism approach with a critical point of view to evaluate the equivalents and appendices (glossaries and bibliographies) show that looking for equivalence in translations needs experts who do not confuse the readers.